Global Magni4icence, or: 4G Networks - Nekrasov, Nikita; Piazzalunga, Nicolò (Symmetry, Integrability and Geometry: Methods and Applications, 2024)
The global magnificent four theory is the homological version of a maximally supersymmetric (8+1)-dimensional gauge theory on a Calabi-Yau fourfold fibered over a circle. In the case of a toric fourfold, we conjecture the formula for its twisted Witten index. String-theoretically, we count the BPS states of a system of 0-2-4-6-8-branes on the Calabi-Yau fourfold in the presence of a large Neveu-Schwarz -field. Mathematically, we develop the equivariant -theoretic DT4 theory by constructing the four-valent vertex with generic plane partition asymptotics. Physically, the vertex is a supersymmetric localization of a non-commutative gauge theory in 8+1 dimensions.